West Virginia - Somervill, Barbara A; Doss, Georgina; Lowe, Suzette; Matusevich, Melissa N (New York Children's Press, 2003)
Takes the reader on a tour of the Mountain State, emphasizing its geography, history, government, and culture
Introducing the Mountain State -- The land of West Virginia -- West Virginia through history -- Governing West Virginia -- The people and places of West Virginia -- West Virginia almanac -- Timeline -- Gallery of famous West Virginians
Includes bibliographical references (p. 76) and index
Hurg
5 8
Keywords: West Virginia -- Juvenile literature; West Virginia